Study on Extraction of Peanut Protein and Oil Bodies by Aqueous Enzymatic Extraction and Characterization of Protein - Chen Liu; Lihua Hao; Fusheng Chen; Chenxian Yang (Journal of Chemistry)
Cell wall degrading enzymes break down the cell wall by degrading the main cell wall components and destroying structure of the cell wall without influencing the protein. Effects of various enzymes (Viscozyme® L, cellulase, hemicellulase, and pectinase) on the molecular weight distribution of peanut protein and yield of peanut protein and oil bodies during an aqueous enzymatic extraction process were investigated in this study. The molecular weight distribution of peanut protein was not changed, and Viscozyme® L was selected to assist peanut protein and oil bodies extraction by the aqueous extraction process. The aqueous enzymatic extraction process was optimized by a signal factor experiment and response surface methodology, and the optimal condition was enzyme hydrolysis temperature of 52°C, solid-liquid ratio of 1 : 4, enzyme concentration of 1.35%, and enzyme hydrolysis time of 90 min. A peanut protein yield of 78.60% and oil bodies yield of 48.44% were achieved under the optimal condition. Compared with commercial peanut protein powder (CPPP), the solubility and foaming properties of peanut protein powder obtained by aqueous enzymatic extraction (AEEPPP) were a little lower. However, the functional properties of foam stability, emulsifying activity, emulsifying stability, water holding capacity, and oil holding capacity of AEEPPP were better than that of CPPP.